Testing mechanical performance of adhesively bonded composite joints in engineering applications: an overview. Issue 14 (26th October 2022) - Budzik, Michal K.; Wolfahrt, Markus; Reis, Paulo; Kozłowski, Marcin; Sena-Cruz, José; Papadakis, Loucas; Nasr Saleh, Mohamed; Machalicka, Klara V.; Teixeira de Freitas, Sofia; Vassilopoulos, Anastasios P.
ABSTRACT: The development of new adhesives has allowed to expand the application of bonding into the most diverse industrial fields. This review article presents the commonly used experimental methods for the investigation of mechanical performance of adhesively bonded joints in the aerospace, wind energy, automotive and civil engineering sectors. In these sectors, due to their excellent intrinsic properties, composite materials are often used along with conventional materials such as steel, concrete and aluminium. In this context, and due to the limitations that the traditional joining techniques present, adhesive joints are an excellent alternative. However, standardized experimental procedures are not always applicable for testing representative adhesive joints in these industries. Lack of relevant regulations across the different fields is often overcome by the academia and companies' own regulations and standards. Additional costs are thus mitigated to the industrial sectors in relation with the certification process which effectively can deprive even the biggest companies from promoting adhesive bonding. To ensure continuous growth of the adhesive bonding field the new international standards, focusing on actual adhesive joints' performance rather than on specific application of adhesive joints are necessary.